2016 public attitudes about agriculture in Colorado: a study by the Colorado Department of Agriculture - Chriestenson, Chad, author; Martin, Michael, author; Thilmany-McFadden, Dawn, author; Sullins, Martha, author; Jablonski, Becca, author; Department of Agricultural and Resource Economics, Colorado State University, publisher (Colorado State University. Libraries, 2016)
This research replicates studies conducted in 1996, 2001, 2006 and 2011 by the Colorado Department of Agriculture partnering with different CSU personnel over the years. In 1996, the Colorado Department of Agriculture and Ag Insights worked with Colorado State University’s Human Dimensions in Natural Resources Unit to develop a survey of Colorado residents to determine the public’s attitudes towards such issues as food prices, food safety, pesticide use, environmental practices, wildlife and agriculture, animal welfare, land use, population growth and agricultural land preservation, among other things. Subsequent reports have then compared the attitudes of Coloradans towards the above-mentioned issues across the years of 1996, 2001, 2006 and 2011. The 2016 survey is intended to add another year of data and comparisons built on these same objectives, but it also seeks to explore some new issues.
In Cooperation with the CSU Department of Agricultural and Resource Economics Colorado State University.
Keywords: agriculture; farms; cropping systems; agriculture products; economic impact